2015
DOI: 10.1145/2808796
|View full text |Cite
|
Sign up to set email alerts
|

Video Interaction Tools

Abstract: Digital video enables manifold ways of multimedia content interaction. Over the last decade, many proposals for improving and enhancing video content interaction were published. More recent work particularly leverages on highly capable devices such as smartphones and tablets that embrace novel interaction paradigms, for example, touch, gesture-based or physical content interaction. In this article, we survey literature at the intersection of Human-Computer Interaction and Multimedia. We integrate literature fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(10 citation statements)
references
References 127 publications
(119 reference statements)
0
10
0
Order By: Relevance
“…Research in human-computer interaction in digital video production dates back to the 1980s, e.g., early work by Mackay and Davenport [35]. A recent survey by Schoefmann [49] highlights the great progress in video content manipulation over the past three decades. Although some researchers explored single user or co-located collaborative editing on a shared computer, a few also address real-time collaborative video editing.…”
Section: Research On Video Interactionmentioning
confidence: 99%
“…Research in human-computer interaction in digital video production dates back to the 1980s, e.g., early work by Mackay and Davenport [35]. A recent survey by Schoefmann [49] highlights the great progress in video content manipulation over the past three decades. Although some researchers explored single user or co-located collaborative editing on a shared computer, a few also address real-time collaborative video editing.…”
Section: Research On Video Interactionmentioning
confidence: 99%
“…[12]. User simulations assume that all users will interact similarly and therefore are not well suited for evaluating interactive search tools that rely heavily on the user [11]. User studies, on the other hand, can consider such specifics of individuals, but are often hard to reproduce, since every study can be influenced by variations in users, tasks, and sometimes datasets.…”
Section: The Need For Multimedia Search Challengesmentioning
confidence: 99%
“…Other work tested face-to-face and video conferencing system for group collaboration in which users show ability to express understanding and attitudes (Isaacs& Tang, 1994). To show a wide variety of research, Schoeffmann, Hudelist & Huber (2015) reported summary of research that incorporates video interaction tools found it works over the last few years have less focus on collaborative video interaction that need users' joint efforts. As such, neither studies have provided audio conference was improved by the use of graphic channels for users' collaboration, nor audio conferencing by different native languages have yet to be conducted.…”
Section: Literature Reviewmentioning
confidence: 99%